1994
DOI: 10.1105/tpc.6.6.863
|View full text |Cite
|
Sign up to set email alerts
|

Immediate early transcription activation by salicylic acid via the cauliflower mosaic virus as-1 element.

Abstract: Transgenic tobacco plants carrying a number of regulatory sequences derived from the cauliflower mosaic virus 35s promoter were tested for their response to treatment with salicylic acid (SA), an endogenous signal involved in plant defense responses. PGlucuronidase (GUS) gene fusions with the full-length (-343 to +8) 35s promoter or the -90 truncation were found to be induced by SA. Time course experiments revealed that, in the continuous presence of SA, the -90 promoter construct (-90 35s-GOS) displayed rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0
26

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 41 publications
9
83
0
26
Order By: Relevance
“…1B). This observation is consistent with previous analyses of PR‐1 gene expression, which occurs late after SA application (Qin et al ., 1994; Ward et al ., 1991). Similar results as for the NIMIN‐1[GUS] construct were obtained in time‐course experiments with the NIMIN‐2[GUS] chimeric gene (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…1B). This observation is consistent with previous analyses of PR‐1 gene expression, which occurs late after SA application (Qin et al ., 1994; Ward et al ., 1991). Similar results as for the NIMIN‐1[GUS] construct were obtained in time‐course experiments with the NIMIN‐2[GUS] chimeric gene (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…Elucidating the time dependent expression profiles of the putative orthologous signature genes under mock induction of the signaling pathways would provide a glimpse into how the genes would respond under pathogen conditions. SA hormone levels in tobacco plants infected with tobacco mosaic virus (Malamy et al, 1990, 1996) parallels the expression profile observed for EgrPR2 in this study (Figure 3A) under application of SA in E. grandis . In contrast to EgrPR2 , EgrPR5 was shown to gradually increase over the time points with a maximum expression level detected at 48 hpt (Figure 3B).…”
Section: Discussionsupporting
confidence: 87%
“…This result suggests that some compo-nents of signal transduction to the CHS promoter may be synthesised early after the onset of irradiation. CPRF mRNA accumulation is induced by CHX treatment in the dark, an observation which has also been reported for other transcription factors involved in hormone-, red light-, and salicylic acid-induced signalling (Lam et al 1989;Ballas et al 1993;Qin et al 1994;Jupin and Chua 1996). The rapid, transient expression of CPRFs, in combination with the CHX-inducible accumulation of their respective mRNAs, makes these transcription factors good candidates for early genes involved in UV light-mediated signalling.…”
Section: The Role Of Cprfs In Uv Light-mediated Signal Transductionsupporting
confidence: 60%